Synthesis, characterization and reactivity study of aluminum compounds incorporating bi- and tri-dentate pyrrole–piperazine ligands. Issue 20 (9th February 2016) - Hu, Ting-Chia; Wu, Ming-Chun; Wu, Shih-Sheng; Hu, Ching-Han; Lin, Chia-Her; Datta, Amitabha; Lin, Tzung-Han; Huang, Jui-Hsien
Abstract : A series of Al derivatives are afforded incorporating substituted bi- and tri-dentate pyrrole–piperazine precursors. The reactivity with small organic molecules and the associated mechanistic details are also reported. Abstract : Substituted bi- and tri-dentate pyrrole–piperazine precursors, C4 H3 NH-[2-CH2 N(CH2 CH2 )2 NPh] (1 ) and C4 H2 NH-2, 5-[CH2 N(CH2 CH2 )2 NPh]2 (2 ) are synthesized and the corresponding Al derivatives are afforded systematically in moderate yield. Reacting one equivalent of1 with AlMe3 in toluene generates an aluminum dimethyl compound, AlMe2 C4 H3 N-[2-CH2 N(CH2 CH2 )2 NPh] (3 ) in satisfactory yield. Similarly, the reaction of two equivalents of1 and AlMe3 affords [AlMeC4 H3 N[2-CH2 N(CH2 CH2 )2 NPh]2 ] (4 ), which on repeating recrystallization in dichloromethane produces [AlMeC4 H3 N[2-CH2 N(CH2 CH2 )2 NPh]2 [NH(CH2 CH2 )2 NPh]] (4a ) in small quantity. Furthermore, reactions of3 with one equivalent of 1, 3-diphenylpropane-1, 3-dione and 2, 6-diisopropylphenol in toluene results in the aluminum methyl compounds, [AlMe(PhCOCHCOPh)C4 H3 N[2-CH2 N(CH2 CH2 )2 NPh]] (5 ) and [AlMe(O-2, 6- i Pr2 C6 H3 )C4 H3 N[2-CH2 N(CH2 CH2 )2 NPh]] (6 ), respectively. Interestingly on fractional recrystallization, compound6 affords the μ 2 -oxo bridged dialuminum compound, [Al(O-2, 6- i Pr2 C6 H3 )C4 H3 N[2-CH2 N(CH2 CH2 )2 NPh]2 (μ-O)] (6a ) while exposed to air. Additionally, the combination of the tridentate pyrrole ligand2 and one equivalent of AlMe3 in toluene produces [AlMe2 C4 H2 N2, 5-[CH2 N(CH2 CH2 )2 NPh]2 ] (7 ). Compounds3, 4a, 5, and6a are subjected to X-ray diffraction analysis to ensure the geometry around the Al atom. Overall, the influences of the new pyrrole-piperazine incorporated N-donor precursors on the structural factors, reactivity with small organic molecules and the associated mechanistic details are discussed.